(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of neck pain among dentists and its association with impaired quality of life (QoL). Study Design: A cross-sectional study. Place and Duration of Study: This study was conducted at the OPD of dental department at Multan Medical and Dental College, Multan, from October 2022 to May 2023. Methods: This research was conducted on 220 dentists selected by non-probability convenient sampling technique without any gender discrimination. Disability due to neck pain was measured using the Neck Disability Index (NDI), gender-stratified Spearman Rank Correlation Coefficient was used to assess the correlation between neck pain intensity and disability due to neck pain. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 23. Results: A total of 220 dentists respond the questionnaire. 27 out of 78 male and 43 out of 142 female are healthy while 51 male and 99 female feel neck pain. 65% male can’t read during NP while 64% female have this disability. Similarly, headache increases NP intensity in female 66% while it is less 58% in male. 44% female and 35% male can’t do personal care during neck pain. Conclusion: Neck pain is common in dentists due to their postural demand in their working environment and it has a significant impact on dental practices. Neck pain had great impact on the daily functions and quality of life of the dentists.